2007
DOI: 10.1007/s11418-007-0195-y
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective activity of Eriobotrya japonica seed extract on experimentally induced gastric lesions in rats

Abstract: The effect of Eriobotrya japonica seed extract (ESE) prepared with 70% ethanol on gastric mucosal injury was investigated. Six experimental models with different action mechanisms were used for the evaluation. Three concentrations of ESE were prepared for each model. ESE administration was initiated 14 days before induction of gastric mucosal injury, and its effect was investigated. ESE inhibited formation of gastric mucosal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…It is well known that the seeds of E. japonica contain a cyanide glycoside, amygdarin, that can be used as an anti-cough traditional medicine in Japan [57]. Furthermore, because anti-oxidant activity [58,59] and hepatoprotective activity [60] have been reported, the seeds are also good candidates for health food together with the leaves. …”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the seeds of E. japonica contain a cyanide glycoside, amygdarin, that can be used as an anti-cough traditional medicine in Japan [57]. Furthermore, because anti-oxidant activity [58,59] and hepatoprotective activity [60] have been reported, the seeds are also good candidates for health food together with the leaves. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ESE has a variety of biological effects [5][6][7][8][9][10][11][12]. Many of these effects are considered to be related to the antioxidant actions of ESE [8].…”
Section: Discussionmentioning
confidence: 99%
“…The final yield of 70% ethanol extract was 108 g. The dried extracts were dissolved with 20 L of distilled water as a stock. The high-performance liquid chromatography (HPLC) profile of ESE was previously reported, including gallic acid and caffeine as major components [9].…”
Section: Plant Materials and Preparation Of Esementioning
confidence: 99%
See 2 more Smart Citations